Impact of trough IgG on pneumonia incidence in primary immunodeficiency: A meta-analysis of clinical studies - Orange, Jordan S.; Grossman, William J.; Navickis, Roberta J.; Wilkes, Mahlon M. (Clinical immunology (Orlando, Fla.), 2010)
Primary immunodeficiency disease (PIDD) associated with hypogammaglobulinemia is typically treated with immunoglobulin replacement therapy. When administered as intravenous immunoglobulin (IVIG), an IgG trough occurs prior to the next replacement dose. While frequently measured, IgG trough levels required to minimize infection risk are not established. To address this question, all available studies evaluating trough IgG and pneumonia incidence in PIDD patients with hypogammaglobulinemia receiving IVIG were quantitatively combined by meta-analysis. Seventeen studies with 676 total patients and 2,127 patient-years of follow-up were included. Pneumonia incidence declined by 27% with each 100mg/dL increment in trough IgG (incidence rate ratio, 0.726; 95% confidence interval, 0.658–0.801). Pneumonia incidence with maintenance of 500mg/dL IgG trough levels (0.113 cases per patient-year) was 5-fold that with 1000mg/dL (0.023 cases per patient-year). This meta-analysis provides evidence that pneumonia risk can be progressively reduced by higher trough IgG levels up to at least 1000mg/dL.